2021
DOI: 10.1002/ehf2.13181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of QRS morphology on response to conduction system pacing after atrioventricular junction ablation

Abstract: Aims His-Purkinje conduction system pacing (HPCSP) utilizing His (HBP) or left bundle branch pacing (LBBP) in patients with atrial fibrillation (AF) and wide QRS duration has not been well studied. We assessed the benefit of left bundle branch block (LBBB) correction during HPCSP in AF patients undergoing atrioventricular junction (AVJ) ablation with LBBB, compared with those with narrow QRS duration. Methods and results This is an observational study in consecutive patients with typical LBBB or narrow QRS dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…A previous study indicated that AF patients with LBBB have greater improvement in LVEF and NYHA class function than patients with narrow QRS from HBP/LBBP after AVJ ablation. LBBP showed similar outcomes to patients with HBP, but with lower pacing thresholds and higher R‐wave amplitude 21 . It is reasonable to consider that HBP and LBBP are the better choice to achieve an optimal activation in the LV, especially in patients with LV dysfunction 22,23 …”
Section: Discussionmentioning
confidence: 88%
“…A previous study indicated that AF patients with LBBB have greater improvement in LVEF and NYHA class function than patients with narrow QRS from HBP/LBBP after AVJ ablation. LBBP showed similar outcomes to patients with HBP, but with lower pacing thresholds and higher R‐wave amplitude 21 . It is reasonable to consider that HBP and LBBP are the better choice to achieve an optimal activation in the LV, especially in patients with LV dysfunction 22,23 …”
Section: Discussionmentioning
confidence: 88%
“…BVP could not maintain synchrony in patients with a native narrow QRS ( 6 ) and leads to non-physiological ventricular activation in AVB patients. Fusion with intrinsic conduction by optimized AV intervals plays an important role in determining the benefit of BVP, which is limited in AF and AVB patients ( 32 ), while this could be achieved by HBP or LBBP with narrow QRS or typical LBBB and HF ( 33 , 34 ). In addition, the role of BVP in patients with AVB and mild-to-moderate impairment in left ventricular function remains controversial, and comparisons of clinical outcomes in such patients with BVP vs. RVP remain mixed ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that permanent HBP with AVN ablation leads to significant improvement in cardiac function in AF patients with narrow QRS who suffered from HF with preserved or reduced ejection fraction. In addition, study 9 has confirmed the efficacy of HPCSP in patients with a wide QRS and narrow QRS. The result show that HPCSP with AVN ablation benefits patients with LBBB by improving LVEF and NYHA class function more than patients with narrow QRS.…”
Section: Pacing Strategy In Af and Hfmentioning
confidence: 81%
“…Under this circumstance, LBBP with LBB capture, but not left ventricular septal pacing, could be another alternative to achieve physiological conduction system pacing and can offer a better safety margin following AVN ablation 4 . Studies have shown that the success rate of LBBP in patients with failure of BVP or HBP is close to 100% 8,9 . HBP and LBBP had similar improvements in symptoms and LV function, which is not inferior to BVP 7,15–17 …”
Section: Feasibility and Safety Of Hpcspmentioning
confidence: 99%